Extracellular vesicles induce minimal hepatotoxicity and immunogenicity. Issue 14 (27th March 2019) - Saleh, Amer F.; Lázaro-Ibáñez, Elisa; Forsgard, Malin A.-M.; Shatnyeva, Olga; Osteikoetxea, Xabier; Karlsson, Fredrik; Heath, Nikki; Ingelsten, Madeleine; Rose, Jonathan; Harris, Jayne; Mairesse, Maelle; Bates, Stephanie M.; et al.
Abstract : The absence of any significant toxicity associated with EVs in vitro and in vivo support the prospective use of EVs for therapeutic applications and for drug delivery. Abstract : Extracellular vesicles (EVs) mediate cellular communication through the transfer of active biomolecules, raising interest in using them as biological delivery vehicles for therapeutic drugs. For drug delivery applications, it is important to understand the intrinsic safety and toxicity liabilities of EVs. Nanoparticles, including EVs, typically demonstrate significant accumulation in the liver after systemic administration in vivo . We confirmed uptake of EVs derived from Expi293F cells into HepG2 cells and did not detect any signs of hepatotoxicity measured by cell viability, functional secretion of albumin, plasma membrane integrity, and mitochondrial and lysosomal activity even at high exposures of up to 5 × 10 10 EVs per mL. Whole genome transcriptome analysis was used to measure potential effects on the gene expression in the recipient HepG2 cells at 24 h following exposure to EVs. Only 0.6% of all genes were found to be differentially expressed displaying less than 2-fold expression change, with genes related to inflammation or toxicity being unaffected. EVs did not trigger any proinflammatory cytokine response in HepG2 cells. However, minor changes were noted in human blood for interleukin (IL)-8, IL-6, and monocyte chemotactic protein 1 (MCP-1). Administration of 5 × 10 10 Expi293F-derived EVs to BALB/c mice did not result in any histopathological changes or increases of liver transaminases or cytokine levels, apart from a modest increase in keratinocyte chemoattractant (KC). The absence of any significant toxicity associated with EVs in vitro and in vivo supports the prospective use of EVs for therapeutic applications and for drug delivery.